The dynamic analysis of offshore mooring terminals - Langley, R. S. (Cranfield University, 1983)
This Thesis investigates the methods which are currently avail- able for the dynamic analysis of Offshore Mooring Terminals, particular regard being paid to Single Point Mooring (SPM) Terminals. Various aspects of the problem are considered in turn, these being the random vibration of non-linear systems, the analysis of catenary mooring lines, buoy dynamics, ship motions, second order (or slow drift) forces and motions, and low frequency motions caused by instabilities. These various aspects are then applied to the dynamic analysis of a Single Buoy Storage (SBS) System and the effect of the method of analysis employed, the system dimensions and the environmental conditions on the computed response is investigated. A Time Domain investigation of the stability of the SBS System in the presence of wind and current alone reveals that the system is only unstable for combinations of wind and current which are unlikely to occur in practise. A static offset position is then assumed and the calculation of the three-dimensional first and second order response to random waves is performed in the Frequency Domain, linear wave theory being used. The first order wave forces are calculated by using strip theory for the tanker and Morison's equation for the buoy. The second order response in surge, sway and yaw is calculated by a reflection coefficient method, these coefficients being obtained from published literature. The non-linear mooring system and the drag forces acting on the buoy are linearised using the equivalent linearisation method, due account being taken of the coupling between the first and second order response. The model developed for the first order response of the system allows the use of a spreading function in the incident wave spectrum. The accuracy of linearisation techniques and the statistics of the second order force and response are also investigated.